Fundamentals of the process of preparing karate competitors in the kata modality (Review) (Revista científica Olimpia, 2021)
In this work, fundamentals of the process of preparing karate competitors in the kata modality are presented, with emphasis on the technical component, based on references from authors in the national and international context; in addition to the review of doctoral and master's theses, articles and bibliographies related to the theory and methodology of sports training, as well as the Comprehensive Karate Athlete Preparation Program.
Keywords: karate; technique; kata; preparation